Pengaruh Penerapan Bahasa Inggris Pada Menu Makanan Terhadap Minat Beli Konsumen Pada Dapur Seblak Bangkinang - Yetti, Dzulhijjah; Rahmad Akbar; Nurkholis Nurkholis; Nofiar. Am, Andri; M. Alkadri Perdana (Politeknik Kampar, 2025)
This study aims to analyze the effect of using English in food menu names on consumer purchase intention at Dapur Seblak Bangkinang. In the globalization era, the use of foreign terms is believed to enhance product appeal, especially among younger consumers. The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to 100 active customers of Dapur Seblak Bangkinang. The results show that using English in menu naming creates a more modern and trendy image, which significantly increases consumers' buying interest. These findings indicate that language strategy in product naming plays a crucial role in shaping consumer perceptions and influencing purchase decisions. Therefore, culinary business owners are encouraged to consider using foreign languages as part of their marketing strategy.